The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1039/c5cp07218b
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium thermodynamics and collective vibrational modes of liquid water in an inhomogeneous electric field

Abstract: In this experiment liquid water is subject to an inhomogeneous electric field (∇ 2 ≈ 10 10 2 ⁄ ) using a high voltage (20 kV) point-plane electrode system. With interferometry it was found that the application of a strong electric field gradient to water generates local changes in the refractive index of the liquid, polarizes the surface and creates a downward moving electro-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…From previous experiments [33,34] it is known that spike-like refractive index changes similar to the ones observed in the present experiment (see Figures 4-6) occur in a needleplate set-up when the high voltage is switched on or off, so during the electrically induced phase transition. These spikes are the kinks, solitons or vortices discussed earlier, and partly consist of both phases.…”
Section: (C)supporting
confidence: 85%
See 2 more Smart Citations
“…From previous experiments [33,34] it is known that spike-like refractive index changes similar to the ones observed in the present experiment (see Figures 4-6) occur in a needleplate set-up when the high voltage is switched on or off, so during the electrically induced phase transition. These spikes are the kinks, solitons or vortices discussed earlier, and partly consist of both phases.…”
Section: (C)supporting
confidence: 85%
“…Previous results from quasi-elastic neutron scattering [30], femtosecond mid-infrared spectroscopy [24], and Raman spectroscopy [33] strongly indicated that neither EHD flow simulation nor molecular dynamic simulations are sufficient to explain some of the macroscopic effects observed in the experiments mentioned. Among these are increased proton mobility and increased molecular vibrational relaxation in the bridge, as well as long-range vibrational coupling among water molecules.…”
Section: Topological Changes In Electrically Stressed Watermentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the bridge bases are locations of strong field gradients [9] , [37] . A Raman investigation [38] has shown that such gradients establish an excited subpopulation of vibrational oscillators far from thermal equilibrium. Hindered rotational freedom due to electric field pinning of molecular dipoles [23] , [38] retards the heat flow and generates a chemical potential gradient responsible for observable changes in the refractive index and temperature, exhibiting local non-equilibrium thermodynamic transient states critical to biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this energy appears to be related to a macroscopic state of water that behaves optically as quasi-liquidcrystals do [13]- [15]. Apparently this energy can be dissipated as infrared radiation [4] [16] or mechanical flow [3] [17]. We will propose that this energy from dissociated water is an important part of blood flow in venules, the spread of action potentials in axons, the heart beat and spreading depression waves and other electrochemical patterns in the brain present in functional syndromes.…”
Section: Introductionmentioning
confidence: 99%